2021
DOI: 10.1002/er.6374
|View full text |Cite
|
Sign up to set email alerts
|

Combination effects of flow field structure and assembly force on performance of high temperature proton exchange membrane fuel cells

Abstract: In this work, a three-dimensional, steady state model was developed by combining mechanical equations, Navier-stokes equation, Maxwell-Stefan equation, and Butler-Volmer equation. This model was used to investigate the influences of flow field structure and assembly force on porosity distribution in gas diffusion layer (GDL), species distribution in GDL, and current density distribution in GDL and membrane by extracting uneven porosity in the GDL from mechanical calculation equation to put in mass transfer cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…The high-temperature PEMFC (HTPEMFC) characteristics have been investigated recently at temperatures over 373 K [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. However, many studies have focused on the R&D of new materials, e.g., membranes and catalysts [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high-temperature PEMFC (HTPEMFC) characteristics have been investigated recently at temperatures over 373 K [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. However, many studies have focused on the R&D of new materials, e.g., membranes and catalysts [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The review reported a comparison of performances among PEMs made of polybenzimidazoles, sulphonated polyether ether ketones and pyridine-based materials operated at high temperatures above 373 K, concluding that it is necessary to perform careful multi-physics modeling of PEM in order to improve H 2 O and thermal management [13]. A numerical study analyzed the distribution of the current density, O 2 and H 2 O concentrations when the assembly pressure was changed [14]. The power generation characteristics were investigated using polarization and power curves and by changing the membrane thickness [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Focused on the research to understand the heat and mass transfer characteristics in HTPEFC, some numerical studies have reported that the temperature-driven H 2 O transport in cathode GDL [15], optimization of electrode thickness to obtain higher performance without high cost [16], assessment of mass transport effect on the performance by 3D multi-physics modeling [17], optimization of GDL focusing the thickness of porosity by non-isothermal 3D model [18] and dynamic simulation for start-up process by non-isothermal 3D model [4]. Some numerical studies [19] [20] [21] have reported analysis on separators to optimize a gas channel considering the widths of top and bottom, e.g. cross-sectional area with a trapezium shape [19], the investigation of power generation performance, reactant and H 2 O saturation distribution using oriented-type flow channels with porous-blocked baffles [20], and the impact of the ratio of channel width to rib width on the performance and mass distribution in the cell [21].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the research on HT-PEMFCs mainly includes membrane material [ 17 , 18 , 19 , 20 , 21 , 22 ], structure design [ 23 ], parameter study [ 24 ], and performance optimization [ 25 ]. Yang et al [ 26 , 27 ] studied the high-temperature proton exchange membrane (PEM) in order to improve the performance of the PEMFC at high temperature.…”
Section: Introductionmentioning
confidence: 99%